Continual Flow of Limbu Pa:la:m Song: A Politeness Principle Perspective - Tumbahang, Mohan Kumar (JODEM: Journal of Language and Literature, 2021)
The paper aims to analyze the Limbu cultural specific song Pa:la:m from the perspective of the politeness principle. It attempts to reply the questions such as how the singing duet follows the communicative implicature and what the rationales or practical implications there are in life. The study design was based on the qualitative one which made the use of non-numerical data. The necessary data were elicited from the textual resources that were recorded in certain books of the Limbu culture. Moreover the data were discussed, analyzed and interpreted in relation to pragmatic theory, a part of linguistics. The analysis of the data showed that the Limbu cultural specific song Pa:la:m has readily followed the principle of politeness. As the Pa:la:m singers have learnt the polite form of speech, they can deal verbal behavior smoothly and successfully. It is expected that this study can help the individuals involving in the pragmatic study of the verbal behavior. In addition, the anthropologists can achieve certain insight into the Limbu ethic culture and the traditional song Pa:la:m.